Ecological Production of Cores - Example from Automotive Branch - Grzincic, Marko; Hlavsa, Petr (Manufacturing Technology Journal, 2014)
The paper informs readers about the latest trends in ecological production of cores for the most demanding castings made of aluminum alloys on example of cylinder heads for combustion engines of the passenger cars. Although the cores bonded with silicates are known since the 60th years of the 20th century, only in recent years the technical progress has undergone such level that the leading producers of cylinder heads are able to deploy the system in serial production. Nemak started solving inorganic systems 12 years ago and today it delivers selected products to its customers and during their production there are cores being used which are joined by ecologic systems. The contribution analyses limiting technical aspects at application of inorganic systems. They replace systems of cold-box and hot/warm-box and it presents in details the benefits of ecological solutions which may be found in final product features. At the same time, it also points at difficulties which are still necessary to be solved.
Keywords: casting; core; binder; inorganic; ecology